Capability Level Measurement Using COBIT 5 Framework (Case Study: PT. Jasa Cendekia Indonesia) - Abdurrahman Harits; Gilang Muhamad Noer; Aris Puji Widodo (Universitas Bina Darma, 2021)
PT. Jasa Cendekia Indonesia is a company engaged in the field of recruitment, training and consulting in the provision of human resources. Currently PT. Jasa Cendekia Indonesia has more than 500 outsourcing employees, puts hundreds of Indonesians into the job market and serves more than 30 multinational companies, of course companies need systems that are able to manage and carry out company work operations. This research study aims to conduct an assessment of Information Technology Governance at PT. Jasa Cendekia Indonesia which focuses on the DSS01 domain (manage operations) is measured using the Capability Level in the Cobit 5 Framework. The results obtained from this assessment are needed as an evaluation and input for improvements to Information Technology Governance at PT. Jasa Cendekia Indonesia in the future. The level of ability of PT. Jasa Cendekia Indonesia in the DSS01 process is at a value of 2.80 while the expected level of ability is at level 3 (established process). The recommendation to reach level 3 is expected to be implemented to improve the performance of PT. Jasa Cendekia Indonesia according to the DSS01 process.